TEKNOLOGI VIRTUAL REALITY: SEBAGAI CARA BARU PRESENTASI PURWARUPA DESAIN INTERIOR - Akhmadi, Akhmadi; Ismiranti, Athifa Sri; Adriyanto, Andreas Rio; Febrianta, Mochamad Yudha (Universitas Mercu Buana, 2024)
Education in the field of design begins with the creation of ideas, thoughts and concepts and ends with the creation of a prototype before being submitted to industry for mass production. The design prototype can be a digital prototype that can be viewed through Virtual Reality (VR) glasses. The urgency of this research is to provide alternative interior design engineering other than using animation and printing technical drawings on drawing paper. The virtual reality method can also provide a more interactive design engineering alternative to see the interior design of a room in more detail in a sense of space experience. This research aims to prove the presence of virtual reality technology as an alternative for creating prototypes from the results of one semester of interior design learning. The research method uses experimental description. Namely, after the screening process for indicators of the sense of space literature, a trial was carried out to measure students' tendencies in assessing their interior design prototypes both before and after using VR technology. The results show findings about how to create virtual reality technology from students' interior design final project. The description of the preference questionnaire also states that they are more likely to agree in experiencing the theory of the sense of immersive space when using VR.